Preparation of the fluorescein reagent for solid-phase oligonucleotide 5'-labelling and its use for the synthesis of fluorescently labelled PCR primers for HIV-1 detection - Dubey, I.Ya.; Fedoryak, O.D.; Tkachak, O.M.; Fedoryak, D.M. (Биополимеры и клетка, 1995)
The preparative synthesis of fluorescein H-phosphonate reagent for solid phase 'labelling of oligonucteotides is described. Fluorescein-labelted thymidine and two PCR primers for HIV-1 detection were synthesized using this reagent. Описано препаративний метод синтезу Н-фосфонатного реагента для флюоресцентного мічення олігонуклеотидів безпосередньо в процесі їх твердофазного синтезу. За допомогою цього реагента синтезовано флюоресцеїн-мічені тимідин та два праймери для ампліфікації дліяики гена HIV-1. Описан препаративный метод синтеза Н-фосфонатного реагента для флюоресцентного мечения олигонуклеотидов непосредственно в процессе пх твердофазного сшпеза. С помощью этого реагента синтезированы флюоресценнмеченные тимидны и два праймера для амплификации участка гена HlV-1.